Openness to Experience, Ethical Leadership, and Innovative Work Behavior. (27th June 2018) - Javed, Basharat; Khan, Abdul Karim; Arjoon, Surendra; Mashkoor, Maria; Haque, Adnan ul
Abstract: Drawing on trait activation theory, we examine ethical leadership as a boundary condition on the relationship between openness to experience and innovative work behavior. We collected data from 291 subordinates and 51 supervisors to test our theoretical model. Our results suggest that openness to experience was positively related to innovative work behavior. Furthermore, this relationship was only significant when ethical leadership was perceived high as compared to low. Our research contributes to the literatures on innovative work behavior and ethical leadership.